Sustained Success at the Olympic Level: Perspectives on Coach-Athlete Relationships from Track & Field Throwing Coaches - Infurna, C. J. (Track Coach, 2022)
The purpose of the present study was to explore how elite level American track & field throwing coaches reflected upon their experiences of producing internationally competitive athletes over a successive period. Qualitative research methods were implemented where 6 elite coaches (1 female, 5 male) participated in semi-structured interviews. The first higher order theme was the incorporation of Positive Coaching. This theme included four subthemes: (a) communication skills, (b) autonomy supportive behaviours, (c) getting to know your athletes, and (d) creating an atmosphere of success. The second higher order theme was Understanding Your Coaching Philosophy. This theme included three subthemes: (a) an established technical model of coaching, (b) lifelong learning, and (c) a peer support system. Findings suggest that coaches would benefit from coach education programs focused on supporting the mental capacity of their athletes when competing on an international stage.